Digital Competency-Based Recruitment and Human Resource Performance in Micro, Small, and Medium Enterprises - Dian Ariani; Sugeng Karyadi; Asep Suherman; Dicky Jhon Anderson Butarbutar; Indra Rustiawan (Indonesian Journal Economic Review (IJER), 2026)
The dynamic development of the global and national economy in recent decades has had a significant impact on the existence and sustainability of micro, small, and medium enterprises. On the one hand, fluctuating economic growth often requires small business owners to continuously adapt to uncertain changes in consumer purchasing power. The purpose of this study is to theoretically analyze digital competency-based recruitment and human resource performance in micro, small, and medium enterprises. To answer or achieve the objectives of this study, a qualitative research approach based on theoretical concepts with the assistance of secondary data sources was used. The research results show that digital competency-based recruitment in micro, small, and medium enterprises is no longer about finding candidates with impressive academic degrees, but rather about finding talent with practical, adaptive skills and the ability to directly impact the business's digital ecosystem. Human resource performance analysis in micro, small, and medium enterprises has unique characteristics compared to large corporations. In the micro, small, and medium enterprise sector, human resources are often required to be multidimensional, with one employee handling several functions, while limited financial resources often lead to the neglect of formal performance appraisal systems.